Gambaran Pelaksanaan Indikator Mutu Syariah Perawat di Rumah Sakit Islam Yogyakarta PDHI - Arlina Dhian Sulistyowati; Sri Handayani; Kasih Nursanti (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2019)
Sharia is the standard quality indicators in Islamic hospitals consisting of indicators of minimum service standard (SPM) Quality Indicators and the compulsory Islamic Sharia. Indicators of the quality of the Sharia has a purpose in an effort to standardize the measurement and documentation of application of Islamic values in the service of the patient. Indicators Quality Syariah consists of 8 quality indicators Sharia SPM which consist of reading basmalah in administering drugs and action, hijab mandatory training for patients, for patients, educational fqih Islami, ECG examination according to gender, the wearing of a hijab nursing mothers , the wearing of hijab in the operating room and scheduling operations outside of prayer time. Indicators of the quality of the sharia is another indicator of the quality of compulsory Shariah which consists of mentoring talqin patients breathe death, reminiscent of the time of prayers and the installation of appropriate gender DC. This research aims to know the description of the implementation of the Sharia quality indicators conducted by nurses in inpatient PDHI Yogyakarta Islamic hospital which reflects the implementation of spiritual services to the patient.Â  This research uses descriptive quantitative research design. The population in this study are all the nurses in inpatient care. The respondents of the research as much as 63 respondents obtained with the Total Sampling techniques by observing the exclusion criteria in research. Instrument research using questionnaires. Analysis of univariate data by using a percentage. The results showed of 63 respondents, a total of 6.3% of the respondents the implementation of Sharia in the category quality indicators are lacking, 38.1% of respondents in the category is good enough and as much as 55, 6% in the category either. The conclusion that can be drawn from this study is the implementation of a quality indicator of the Sharia Islamic in PDHI Yogyakarta Hospital in the category of good.